Opportunities for neuromorphic computing algorithms and applications - Schuman, Catherine D.; Kulkarni, Shruti R.; Parsa, Maryam; Mitchell, J. Parker; Date, Prasanna; Kay, Bill (Nature Computational Science, 2022)
Neuromorphic computing technologies will be important for the future of computing, but much of the work in neuromorphic computing has focused on hardware development. Here, we review recent results in neuromorphic computing algorithms and applications. We highlight characteristics of neuromorphic computing technologies that make them attractive for the future of computing and we discuss opportunities for future development of algorithms and applications on these systems. There is still a wide variety of challenges that restrict the rapid growth of neuromorphic algorithmic and application development. Addressing these challenges is essential for the research community to be able to effectively use neuromorphic computers in the future.